Establishing objective benchmarks in robotic virtual reality simulation at the level of a competent surgeon using the RobotiX Mentor simulator. Issue 1111 (6th March 2018) - Watkinson, William; Raison, Nicholas; Abe, Takashige; Harrison, Patrick; Khan, Shamim; Van der Poel, Henk; Dasgupta, Prokar; Ahmed, Kamran
Abstract: Background: To establish objective benchmarks at the level of a competent robotic surgeon across different exercises and metrics for the RobotiX Mentor virtual reality (VR) simulator suitable for use within a robotic surgical training curriculum. Methods: This retrospective observational study analysed results from multiple data sources, all of which used the RobotiX Mentor VR simulator. 123 participants with varying experience from novice to expert completed the exercises. Competency was established as the 25th centile of the mean advanced intermediate score. Three basic skill exercises and two advanced skill exercises were used. Setting: King's College London. Participants: 84 Novice, 26 beginner intermediates, 9 advanced intermediates and 4 experts were used in this retrospective observational study. Results: Objective benchmarks derived from the 25th centile of the mean scores of the advanced intermediates provided suitably challenging yet also achievable targets for training surgeons. The disparity in scores was greatest for the advanced exercises. Novice surgeons are able to achieve the benchmarks across all exercises in the majority of metrics. Conclusion: We have successfully created this proof-of-concept study, which requires validation in a larger cohort. Objective benchmarks obtained from the 25th centile of the mean scores of advanced intermediates provide clinically relevant benchmarks at the standard of a competent robotic surgeon that are challenging yet also attainable. That can be used within a VR training curriculum allowing participants to track and monitor their progress in a structured and progressional manner through five exercises. Providing clearly defined targets, ensuring that a universal training standard has been achieved across training surgeons.